Nurses' voice behaviour: The influence of humble leadership, affective commitment and job embeddedness in China. (20th April 2021) - Zhou, Xiang; Wu, Zhen; Liang, Dandan; Jia, Ruiying; Wang, Meijie; Chen, Chaoran; Lu, Guangli
Abstract: Aim: To test the influence of humble leadership, job embeddedness and affective commitment on the voice behaviour of nurses. Background: A nurse's voice behaviour is regarded as an important measure to identify and solve problems in medical institutions, and improve patients' satisfaction. It is urgent to pay sufficient attention to nurses' advice to determine which factors can stimulate enthusiasm in this area. Methods: This study is a cross‐sectional study involving 598 nurses. Results: The results showed that humble leadership, job embeddedness, affective commitment and voice behaviour were significantly positively correlated. Job embeddedness played a partial mediating role in humble leadership and affective commitment; meanwhile, affective commitment also partially mediated the influence of job embeddedness on voice behaviour. Conclusions: Humble leadership was the key to improve the voice behaviour of nurses; as a mediating mechanism, job embeddedness and affective commitment further explained how humble leadership promoted the voice behaviour of nurses. Implications for Nursing Management: The effects of humble leadership, job embeddedness and affective commitment to voice behaviour could be used to guide the management of clinical nurses. In particular, the humble leadership style perceived by nurses and the enhanced emotional connection with the organisation would contribute to the generation of voice behaviour.